CURRENT CHALLENGES AND SOLUTION APPROACHES IN EMPIRICAL ENGINEERING DESIGN RESEARCH – A WORKSHOP FOR EMPIRICAL RESEARCH. (May 2020) - Üreten, S.; Eisenmann, M.; Nelius, T.; Garrelts, E.; Krause, D.; Matthiesen, S.
Abstract: The requirements on validity for studies in design research are very high. Therefore, this paper aims at identifying challenges that occur when setting up studies and suggests solution strategies to address them. Three different institutes combining their experience discussed several studies in a workshop. Resulting main challenges are to find a suitable task, to operationalise the variables and to deal with a high analysis effort per participant. Automation in data evaluation and a detailed practical guideline on studies in design research are considered necessary.